Fraud Prevention: Exploring the Contributions of Forensic Accounting, Investigative Auditing, and Whistleblowing Effectiveness - Riadi, Sugeng; Aprilian, Puja (International Journal of Law Policy and Governance, 2024)
This research is aimed at investigating whether fraud prevention is affected by factors such as forensic accounting, investigative audits, and the effectiveness of the whistleblowing system. Data was collected through a questionnaire survey administered to all auditors employed by the State Development Audit Agency of Riau Islands. The gathered data underwent a series of assessments, including validity tests, reliability tests, and classical assumption tests. The research employed a quantitative approach, utilizing multiple linear regression analysis for data analysis. The findings of this study reveal that forensic accounting significantly influences fraud prevention, whereas investigative audits and the effectiveness of the whistleblowing system do not exhibit a significant impact on fraud prevention.